Estimación de un modelo econométrico para determinar el efecto de acciones de marketing en ventas de productos de cuidado personal en Colombia - Ana M. Arboleda; Julio C. Alonso (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2016)
– The purpose of this study is to show marketing practitioners how to use econometric models to assess the effect of marketing actions. We use a database that includes the four competitors of a personal care product in Colombia with limited information for a period of six years. The study evaluates the effects of marketing actions on sales revenues for the three product subcategories: premium, midprice, and value. The results show that these effects are different for the three subcategories. This suggests that there is no general model to predict the consequences of marketing actions on sales revenues; marketers need to use statistical methods to assess the effect of their decisions. Finally, although our results cannot be extrapolate to other product categories or countries, our approach can be used to assess the impact of marketing actions on sales revenues in other product categories and industries.
Keywords: M10; M31; C23; 330; marketing actions; competitive dynamics; panel data; mass consumption products